(untitled) (Estudios Humanísticos. Historia, 2015)
Nuestro trabajo se centra en la prestación de cuidados llevado a cabo por el hospital de Nuestra Señora de la Visitación da vila de Caminha, ubicado en el distrito de Viana do Castelo, y dedicado a la atención de personas desfavorecidas. Tomándo como ejemplo la actividad desarrollada por otras instituciones similares en del siglo XIX, buscaremos analizar la organización y las reglas de funcionamiento de este hospital, la actividad desarrollada por los diferentes los profesionales que prestaban servicio, la tipología de los pacientes, con especial atención a los grupos profesionales a los que pertenecían, y finalmente, las enfermedades que provocaron su internamiento. Abstract: Our communication focuses on sources that allow knowing poverty and the poor in northern Portugal, as well as the support mechanisms used by state and welfare institutions to mitigate the difficulties faced by poorest. The documental funds of civilian governments and administrations of the county are of increasing importance to social historians, along with the documentation produced by the Misericórdias and other brotherhoods. In the particular case of Viana do Castelo, from 1855, the newspapers also become a source of information of undeniable interest to understand the nineteenth-century society and its problems. We believe that a more complete and comprehensive poverty will be achieved through the intersection of sources from different documental funds.